2014
DOI: 10.3747/pdi.2013.00124
|View full text |Cite
|
Sign up to set email alerts
|

The Role of an Integrated Care Model for Kidney Disease in the Development of Peritoneal Dialysis: A Single-Center Experience in China

Abstract: Peritoneal dialysis plays a crucial role in the integrated care of patients with end-stage renal disease (ESRD). In this paper, we retrospectively analyzed the quality indicators of peritoneal dialysis (PD) in 712 patients from our center who underwent PD between 2004 and 2011. In 43% of patients, follow-up was undertaken every 3 months at our outpatient department, and 54% patients were followed up by both our hospital and other local hospitals. The patient survival rate at 1, 3 and 5 years was 96.3%, 85.4% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
1
10
0
2
Order By: Relevance
“…Our technique survival rates were lower than those reported by Isla et al from the Limpopo province of South Africa [22] and from China and Canada [11,23,24], but are similar to those reported from the USA [16] and Mexico [25] ( Table 6). Most of these studies, including ours, reported survival in patients starting PD (from day 0).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our technique survival rates were lower than those reported by Isla et al from the Limpopo province of South Africa [22] and from China and Canada [11,23,24], but are similar to those reported from the USA [16] and Mexico [25] ( Table 6). Most of these studies, including ours, reported survival in patients starting PD (from day 0).…”
Section: Discussionsupporting
confidence: 82%
“…Most of these studies, including ours, reported survival in patients starting PD (from day 0). However, the Mexican study [25] included only patients who had been established on PD for one month and one of the studies from China [24] included only patients who had been on PD for three months. We considered it * An informal dwelling (or "shack") is defined by Statistics South Africa [33] as a makeshift structure not approved by a local authority and not intended as a permanent dwelling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are encouraged to visit the dialysis facility regularly for routine management and to see the nephrologists. The suggested PDC interval for PD patients is 1-3 months in the United States and 1-6 months in China [13,18,19]. The optimal PDC interval and its impact on clinical outcomes for PD patients remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed reasons behind the growth of PD in China are discussed in a separate section (below). University hospitals that already had a PD research background showed the fastest growth in their PD programs and reported outstanding clinical outcomes compared with less experienced centers (15)(16)(17)(18)(19). In papers S20 YAO et al…”
Section: Growth Of Chinese Pd Research Internationally and Locallymentioning
confidence: 99%